2010
DOI: 10.1363/3600610
|View full text |Cite
|
Sign up to set email alerts
|

Caring for Women with Abortion Complications in Ethiopia: National Estimates and Future Implications

Abstract: Women treated for moderate/severe complications 23,765 (21,447-26,084) Women hospitalized for complications 13,332 (11,593-15,071) Complications per 1,000 women of reproductive age 3.49Complications per 100 live births 1.96Deaths per 100,000 women treated in public hospitals for postabortion complications 628 (163-1,092)Deaths in health facilities due to unsafe abortion 100 (24-175)Notes: Hospitalization refers to a stay of at least 24 hours. Rates and ratios are calculated using data on the numbers of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 12 publications
4
89
0
Order By: Relevance
“…Thus, induced abortion-related complications are a significant problem in the DRC, and this observation is consistent with the results of many other studies that were conducted in developing countries [11–13, 16, 23, 2632]. It should also be noted that the lowest rates of mortality due to induced abortions are observed in countries where post-abortion care units have been established [3339]. …”
Section: Discussionsupporting
confidence: 89%
“…Thus, induced abortion-related complications are a significant problem in the DRC, and this observation is consistent with the results of many other studies that were conducted in developing countries [11–13, 16, 23, 2632]. It should also be noted that the lowest rates of mortality due to induced abortions are observed in countries where post-abortion care units have been established [3339]. …”
Section: Discussionsupporting
confidence: 89%
“…Consistent findings were obtained in previous studies in Ethiopia [33], Ghana [37] and South Africa [38], where abortion was found to be high among older women. On the contrary, other studies in Ghana, Kenya, Nigeria, and Ethiopia [3942] have found that the prevalence of abortion is high among younger women compared to older ones. In many settings, it is alleged that distribution by age of abortion is high among women in the youngest age groups who want to postpone childbearing and women at the end of their childbearing years, who believe they cannot get pregnant at that age, are most likely to get induced abortions.…”
Section: Discussionmentioning
confidence: 81%
“…Providing women with referrals to health facilities was an integral part of the training provided, yet even where this option exists, as it does in some parts of Zambia, some women are too ashamed, afraid or lack the knowledge or ability to navigate the formal health system to obtain a legal abortion as has also been found in studies in Cambodia, Ethiopia and South Africa. 6,[13][14][15] Ensuring that pharmacy workers reflect on their responsibility to respect women's autonomy and choices and provide them with evidence-based information on their options, including self-induction, to mitigate as much harm as possible, was also an integral component of the training provided.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%